Predictors for readmission risk in schizophrenia: insights from a Saudi Arabian cohort - Alharthi, Mahmoud A.; Al-Raddadi, Rajaa M.; Alfakeh, Sulhi A. (Frontiers in Psychiatry, 2025)
BackgroundThe readmission of individuals with schizophrenia to inpatient care can pose significant challenges and disturb the lives of both patients and their families, as well as the functioning of mental health care systems. Despite the growing prevalence of schizophrenia, there is limited research focused on the predictors of readmission within the Saudi Arabian context.ObjectivesThe primary objective of this research is to assess the readmission rate for patients who have been diagnosed with schizophrenia, as well as to determine the associations between socio-demographic factors and the risk of readmission for these patients.MethodologyIn a retrospective cohort study, 145 individuals who were admitted to the Eradah and Mental Health complex in Jeddah since July 1st to December 31st in 2018 were recruited. Data on socio-demographic characteristics, medical history, medication adherence, and follow-up care were analyzed to determine their association with one-year readmission rates.ResultsFindings revealed that male participants comprise 84.8% of the sample size. Moreover, 5.5% of the patients were employed, with the larger proportion being unemployed. The overall one-year readmission rate was 36.6%. The Key predictor of readmission included the number of previous admissions, length of hospital stay and frequency of outpatient follow-up visits. After controlling to other variables in a multivariate model, the length of stay was not statistically significant, despite appearing to be related to readmission in the unadjusted analysis. The probability of readmission was significantly increased by inadequate follow-up, illustrating the vital role of continuous post- discharge care.ConclusionsAccording to recent research, improving the transfer from inpatient psychiatric care to outpatient care may lower the risk of readmissions and prevent future hospitalization. The results emphasize the importance of specific treatments in minimizing readmission rates among schizophrenia patients in Saudi Arabia.